2020
DOI: 10.1051/0004-6361/201935846
|View full text |Cite
|
Sign up to set email alerts
|

Hot WHIM counterparts of FUV O VI absorbers: Evidence in the line-of-sight towards quasar 3C 273

Abstract: Aims. We explore the high spectral resolution X-ray data towards the quasar 3C 273 to search for signals of hot (∼ 10 6−7 K) X-rayabsorbing gas co-located with two established intergalactic FUV O vi absorbers. Methods. We analyze the soft X-ray band grating data of all XMM-Newton and Chandra instruments to search for the hot phase absorption lines at the FUV predicted redshifts. The viability of potential line detections is examined by adopting the constraints of a physically justified absorption model. The WH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…Heckman et al (2002) and Bordoloi et al (2017) (and references therein) show that O VI observed in the intergalactic medium, CGM of galaxies, and the Milky Way halo can be explained by radiative cooling models. These models agree with observations and simulations showing complex, multiphase structures at the interfaces between hot and cold gas (Oppenheimer & Davé 2009;Churchill et al 2012;Pachat et al 2016;Narayanan et al 2018;Ahoranta et al 2020).…”
Section: Introductionsupporting
confidence: 89%
“…Heckman et al (2002) and Bordoloi et al (2017) (and references therein) show that O VI observed in the intergalactic medium, CGM of galaxies, and the Milky Way halo can be explained by radiative cooling models. These models agree with observations and simulations showing complex, multiphase structures at the interfaces between hot and cold gas (Oppenheimer & Davé 2009;Churchill et al 2012;Pachat et al 2016;Narayanan et al 2018;Ahoranta et al 2020).…”
Section: Introductionsupporting
confidence: 89%
“…Some extragalactic O vii, O viii, and Ne ix X-ray-line absorption has been found with current instruments, but with difficulty. Kovács et al (2019) found O vii absorption by stacking Xray observations centred on H i absorption systems near massive galaxies, though they targeted large-scale structure filaments rather than the CGM, while Ahoranta et al (2020) found O viii and Ne ix at the redshift of an O vi absorber. Bonamente et al (2016) found likely O viii absorption at the redshift of a broad Lyman α absorber.…”
Section: Introductionmentioning
confidence: 99%
“…Until such missions are launched, progress can be made with deep follow-up of FUV absorption lines with current X-ray instruments. The simulations can also help interpret the small number of absorbers found with current instruments (e.g., Nicastro et al 2018;Kovács et al 2019;Ahoranta et al 2020); e.g. Johnson et al (2019) used galaxy information to re-interpret the lines found by Nicastro et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, a 4.5σ combined significance, or 3.2σ each, for 40 spectral elements searched in the spectrum results in a 0.08% chance of the fluctuations being random. A reduced blind line search region could be achieved with a low redshift GRB as the background source or with an a priori redshift from UV data or known galaxy locations, as in Kovács et al (2019) and Ahoranta et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kovács et al (2019) quotes a 3.3σ detection of O vii towards H1821+643 from a stacked spectrum of Chandra observations with an 8 Ms total exposure. A&A 642, A24 (2020) Ahoranta et al (2020) performed spectral analysis of Chandra and XMM-Newtown observations at previously determined FUV redshifts, yielding two X-ray line candidates of Ne ix Heα and O viii Lyα at a combined significance of 3.9σ. In spite of the large observational efforts, only these few marginal detections have been achieved so far.…”
Section: Introductionmentioning
confidence: 99%